(untitled) (Global Journal of Human-Social Science, 2016)
The purpose of this study was to investigate the possibility of meeting the needs of Taiwanese teachers trained at the colleges and universities in Taiwan. This study combined both qualitative and quantitative methods, using a narrative case study methodology and survey questionnaire. This paper only presents the quantitative results to maintain the interest of target audience..